A new species of Leptolalax (Anura: Megophryidae) from central Vietnam - Rowley, Jodi J. L.; Hoang, Huy Duc; Dau, Vinh Quang; Le, Duong Thi Thuy; Cao, Trung Tien (Zootaxa, 2012)
We describe a new species of Leptolalax from central Vietnam. Leptolalax firthi sp. nov. is distinguished from its congeners bya combination of the following characters: an absence of distinct dark brown or black dorsolateral markings; toes with rudimen-tary webbing and wide lateral dermal fringes in males and weak or absent lateral dermal fringes in females; most males withwide lateral dermal fringes on Finger II; medium size (26.4–29.2 mm in 21 adult males, 25.7–36.9 mm in 14 females); and nearimmaculate white chest and belly. The male advertisement call of the new species, consisting of 2–5 notes with a dominant fre-quency of 5.4–6.6 kHz (at 18.3–21.2º C) is also unique among Leptolalax species for which calls are known. Uncorrectedsequence divergences between L. firthi and all homologous 16S rRNA sequences available were >10%. At present, the newspecies is known from montane evergreen forest between ~860–1720 m elevation in Kon Tum and Quang Nam Provinces. Theextreme sexual dimorphism observed in L. firthi in terms of lateral dermal fringing, a morphological character often used to dis-tinguish Leptolalax species, highlights the importance of ensuring interspecific comparisons in the genus are performed separately for each sex.